2001
DOI: 10.1093/carcin/22.11.1877
|View full text |Cite
|
Sign up to set email alerts
|

Rat oesophageal cytochrome P450 (CYP) monooxygenase system: comparison to the liver and relevance in N-nitrosodiethylamine carcinogenesis

Abstract: N-nitrosodiethylamine (NDEA) is able to induce tumours in the rat oesophagus. It has been suggested that this could be due to tissue specific expression of NDEA activating cytochrome P450 enzymes. We investigated this by characterizing the oesophageal monooxygenase complex of male Wistar rats and comparing it with that of the liver. Total amount of cytochrome P450, NADPH P450 reductase, cytochrome b5 and cytochrome b5 reductase of the oesophageal mucosa was approximately 7% of what was found in the liver. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Only the CM of contracting C2C12 myotubes was able to reduce the expression of Cyp2a3 in FAO hepatocytes. It should be noted however that this effect was not observed in primary hepatocytes and that the Cyp2a3 gene is usually not very highly expressed in rat liver 39 . The biological relevance of the down-regulation of Cyp2a3 in FAO hepatocytes by EPS-CM therefore remains to be established.…”
Section: Discussionmentioning
confidence: 89%
“…Only the CM of contracting C2C12 myotubes was able to reduce the expression of Cyp2a3 in FAO hepatocytes. It should be noted however that this effect was not observed in primary hepatocytes and that the Cyp2a3 gene is usually not very highly expressed in rat liver 39 . The biological relevance of the down-regulation of Cyp2a3 in FAO hepatocytes by EPS-CM therefore remains to be established.…”
Section: Discussionmentioning
confidence: 89%
“…These compounds are considered to be critical environmental factors influencing cancer risk in humans, as they widely exist in the environment, in certain occupational settings, in food stuffs such as meat products and milk, as well as an endogenous formation in the human body from dietary components 3. A variety of studies have demonstrated that N-nitroso compounds could cause a wide range of tumors in many animal species 4-6. Nitrosodiethylamine (NDEA) is one of the most potent chemical hepatocarcinogens of this class, which can induce a variety of liver lesions in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of NDEA metabolising CYPs has been reported as a major determinant of the development of tumours in certain tissues. For example, Ribeiro Pinto et al (2001) found that CYP2E1 was exclusively expressed in liver, while CYP2A3 was only found in the oesophagus; the Km for NDEA N-deethylase in oesophageal microsomes was about one-third of that calculated in liver microsomes (Ribeiro Pinto et al, 2001) and similar results were obtained using tissue slices (Ribeiro Pinto, 2000). Results from these studies suggest that in rat oesophagus, CYP2A3 is mainly responsible for NDEA bioactivation and may induce tumour formation even at low doses.…”
Section: In Vitro Studiesmentioning
confidence: 71%